“Am I Man Enough?”: Diskriminasi terhadap Identitas Transpria Muda (Studi Analisis Video YouTube Trans Men Talk Indonesia) - Himas Nur Rahmawati (Jurnal Studi Pemuda, 2021)
Discourse contestation around youth in Indonesia still rarely touches issues related to gender minority identities, transman (transgender man) is one of them. This research discusses the complexity of the problems and situations of discrimination experienced by young transmen in Indonesia. The research was conducted by analyzing the YouTube video of Trans Men Talk Indonesia entitled "Transmen Indonesia: We are Exist, Real and Deserved to be Happy too. Part 1. " This community, which was founded by young transmen, has dialogued YouTube as an arena for self-articulation and a performative space to show their agency. This study uses a qualitative content analysis method by selecting thematic narratives and visual texts. The findings that resulted are young transmen experiencing a discrimination which can be described through three domains, namely in (1) dating life; (2) occupation, as well as; (3) scarcity of safe space. Collective solidarity for the transmen community is an urgency. This effort is made in order to create an inclusive space that is commensurate with those who are often carried out by the power of cisnormativity.